A new perforated core buckling restrained brace. (15th February 2015) - Piedrafita, D.; Cahis, X.; Simon, E.; Comas, J.
Highlights: Slotted buckling restrained brace. Machined yielding core and slotted restraining unit. Design methodology of the yielding core. Testing under AISC 341-05 and EN15129 protocols. Simulation of the hysteretic behaviour using commercial finite element program. Abstract: The Perforated Core Buckling Restrained Brace (PCBRB) is a new energy dissipation device for the seismic design of buildings. Its core consists of a perforated steel yielding plate which is guided and partially stabilized by the restraining unit. The core is mechanized to obtain two yielding lateral bands which are connected by several equidistant stabilizing bridges. The lateral bands are designed to yield to axial forces, as conventional BRBs do, so the force and the displacement at the yielding point can be calculated by the usual expressions of conventional buckling restrained braces, based on uniform strain distribution. To distribute the stabilizing bridges along the core, an expression based on Euler's formulation is proposed. Under this formulation two types of specimens have been designed and tested (Type I and Type II) using three different loading protocols. The Type I specimens exhibited a stable response, while the Type II specimens suffered a progressive loss of compression capacity produced by the local buckling. Finally, the hysteretic behaviour of the tested braces and a large scale brace has been analysed with an FEM model which considers the interaction between the core and the encasing member. The model reproduces the hysteretic response during the first cycles and the influence of friction on the axial strain distribution along the yielding core.